(untitled) (Conferencea, 2023)
This thesis explores the specific challenges of achieving equivalences in literary translation between Uzbek and English novels. It emphasizes the importance of understanding linguistic, cultural, and contextual factors unique to these languages and cultures. The study argues that successful translations between Uzbek and English novels require a comprehensive approach that preserves both the meaning and literary essence of the original text while navigating the specific challenges posed by these language pairs.